The Generation of 150 km Echoes Through Nonlinear Wave Mode Coupling - William J. Longley (Geophysical Research Letters)
Abstract A fundamental problem in plasma turbulence is understanding how energy cascades across multiple scales. In this paper, a new weak turbulence theory is developed to explain how energy can be transferred from Langmuir and Upper‐Hybrid waves to ion‐acoustic waves. A kinetic approach is used where the Boltzmann equation is Fourier‐Laplace transformed, and the nonlinear term is retained. A unique feature of this approach is the ability to calculate power spectra at low frequencies, for any wavelength or magnetic aspect angle. The results of this theory explain how the predominant type of 150‐km radar echoes are generated in the ionosphere. First, peaks in the suprathermal electron velocity distribution drive a bump‐on‐tail like instability that excites the Upper‐Hybrid mode. This excited wave then couples nonlinearly to the ion‐acoustic mode, generating the ∼10 dB enhancement observed by radars. This theory also explains why higher frequency radars like ALTAIR do not observe these echoes.